A retrospective cohort review of prescribing in hospitalised patients with heart failure using Beers criteria and STOPP recommendations. (17th March 2022) - Beezer, Janine; Roe, Lisa; Husband, Andy
Abstract: Background: With an ageing population and multimorbidity on the rise, polypharmacy is also increasing. Polypharmacy is common in patients with heart failure, possibly due to the application of evidence‐based therapy to improve prognosis and symptoms. Objectives: To identify potentially inappropriate medications according to Beers criteria and the STOPP screening tool; To assess if the recommendations generated from applying these tools could have potentially unintended harmful outcomes in the context of a heart failure diagnosis. Method: Medications for 30 patients, aged ≥75 years with an existing diagnosis of reduced ejection fraction (HFrEF) were extracted from the National Heart Failure Database. Patient medications were reviewed at the point of admission and recommendations documented and reviewed. Results: Patients were prescribed an average of 11 medicines. Beers criteria generated 22 recommendations, of which 27% (6) could have potential detrimental effects on patient outcomes. STOPP screening generated 54 recommendations of which 65% (35) were considered to have potentially unintended harmful consequences in patients with heart failure. Conclusions: Both guidelines for the review of potentially inappropriate medicines generated recommendations that could have potentially detrimental effects on heart failure management when considering patients with HFrEF.